Класифікація загроз економічній безпеці суб’єктів господарювання - Білоусов, Є. М. (Baltic International Academy, 2019)
Наукова робота присвячена вивченню загроз економічній безпеці суб'єктів господарювання, проведена і запропонована їх авторська класифікація з метою ефективного попередження, усунення та нейтралізації загроз економічній безпеці суб'єктів господарювання. // The scientific work is devoted to the study of threats to the economic security of business entities, their author classification has been conducted and proposed with the aim of effectively preventing, eliminating and neutralizing threats to the economic security of business entities.
Keywords: економічна безпека; суб'єкти господарювання; загрози економічній безпеці; economic security; economic security of business; threats to the economic security of business entities